2019
DOI: 10.1111/hae.13848
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, open‐label study of emicizumab given every 2 or 4 weeks in children with severe haemophilia A without inhibitors

Abstract: Introduction Emicizumab is a recombinant humanized bispecific monoclonal antibody mimicking the cofactor function of activated factor VIII. Aim In this multicentre, open‐label study (HOHOEMI), we evaluated the efficacy, safety and pharmacokinetics of emicizumab in Japanese paediatric patients aged <12 years with severe haemophilia A without factor VIII (FVIII) inhibitors. Methods Emicizumab was administered subcutaneously, with four loading doses of 3 mg/kg every week followed by maintenance doses of 3 mg/kg e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
195
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(222 citation statements)
references
References 18 publications
13
195
1
2
Order By: Relevance
“…The trough levels of emicizumab in plasma at clinically therapeutic doses have been estimated to be approximately 30 to 80 μg/mL. [14][15][16][17][18] In the present study, to reflect pathogenic mechanism(s) of TMA and to evaluate current risk management for emicizumab-related TMA in clinical settings, a concentration of 100 µg/mL as the maximum dose, comparable to the plasma emicizumab concentration at a high-dose regimen (C3-cohort) in the phase 1/2 study, 12,13 was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…The trough levels of emicizumab in plasma at clinically therapeutic doses have been estimated to be approximately 30 to 80 μg/mL. [14][15][16][17][18] In the present study, to reflect pathogenic mechanism(s) of TMA and to evaluate current risk management for emicizumab-related TMA in clinical settings, a concentration of 100 µg/mL as the maximum dose, comparable to the plasma emicizumab concentration at a high-dose regimen (C3-cohort) in the phase 1/2 study, 12,13 was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…To date, clinical experience on the use of emicizumab for the treatment of PUPs with HA is only described in a single PUP who was enrolled at 4 months of age in the Q4W cohort of the HOHOEMI clinical trial. 33 This PUP experienced no bleeds during a 24-week period followup. Although this result seems promising, prospective studies using emicizumab prophylaxis in PUPs may be required to better assess the outcome of such novel therapeutic strategy in pediatric patients with severe HA (Table 2).…”
Section: Efficacy In Children Without Fviii-inhibitorsmentioning
confidence: 83%
“…Results were concordant with those observed in adult patients, revealing that through plasma emicizumab concentrations were maintained at approximately 50 µg/mL, 45 µg/mL, and 38 µg/mL with QW, Q2W, and Q4W dosing, respectively (Figure 1). 32 Recently, the HOHOEMI study, a Japanese multicenter non-randomized trial, reported pharmacokinetic data of emicizumab administered subcutaneously at a maintenance dose of 3 mg/kg Q2W (n=6 patients) or 6 mg/kg Q4W (n=7 patients) in HA pediatric patients without FVIII-inhibitors, 33 including only one previously untreated patient (PUP), after receiving a loading dose of 3 mg/kg QW subcutaneously for the first 4 weeks of treatment. The mean trough plasma concentrations of emicizumab were approximately 48 μg/mL at the completion of the loading dose in both cohorts, which were comparable with those in adult and adolescent patients receiving the same Q2W or Q4W regimen in HAVEN 2, HAVEN 3 and HAVEN 4 studies.…”
Section: Pharmacology Mode Of Action and Pharmacokinetics Of Emicizmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, clinical experience with noninhibitor pediatric patients receiving emicizumab prophylaxis is available from only a small number of centers. We have recently reported the interim results from a multicenter open‐label phase 3 study of pediatric noninhibitor patients <12 years old treated with emicizumab every 2 and 4 weeks 48 . In this study, the median age of participants was 6.6 years (1.5‐10.7) in the every 2 weeks cohort and 4.1 years (0.3‐8.1) in the every 4 weeks cohort.…”
Section: Questions For the Wider Use Of Emicizumab In The Postmarketimentioning
confidence: 93%